2017
DOI: 10.5152/npa.2017.19343
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Turkish Version of the 8-Item Parkinson’s Disease Questionnaire

Abstract: Introduction: Symptomatic control and improvement of healthrelated quality of life (HRQoL) is a key feature of the management of patients with Parkinson's disease (PD). The 39-item Parkinson's Disease Questionnaire (PDQ) and its short version, PDQ-8, validated diseasespecific patient-reported instruments, have been highly recommended to use for assessing HRQoL in patients with PD. The aim of this study was to assess the reliability and validity of the Turkish version of the PDQ-8. Methods: Eighty-three patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…In this study, the independent PDQ-8 revealed acceptable internal consistency reliability (α = 0.88) and the item-total correlations (0.48-0.73) based on the acceptable points of Cronbach's α of ≥ 0.7 and the item-total correlation coefficient of ≥ 0.20 [9]. This result may be supported by the consistent previous reports [8,14,19,[21][22][23]. The Kappa coefficient demonstrated a moderate inter-rater reliability between the independent and nested PDQ-8 instruments.…”
Section: Journal Of Health Informatics and Statisticssupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, the independent PDQ-8 revealed acceptable internal consistency reliability (α = 0.88) and the item-total correlations (0.48-0.73) based on the acceptable points of Cronbach's α of ≥ 0.7 and the item-total correlation coefficient of ≥ 0.20 [9]. This result may be supported by the consistent previous reports [8,14,19,[21][22][23]. The Kappa coefficient demonstrated a moderate inter-rater reliability between the independent and nested PDQ-8 instruments.…”
Section: Journal Of Health Informatics and Statisticssupporting
confidence: 87%
“…[7,14,19]. Two methods were used for the linguistic validation and cross-cultural adaptation of the PDQ-8 [8,14,[20][21][22][23]. The first one is to use the 8 items derived from the existing PDQ-39 data [7,14,19].…”
Section: Convergent Validity and Criterion Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…PHA-39'un kısa formu olarak geliştirilen PHA-8'in (70), Kahraman ve ark. tarafından, Türkçe versiyonunun testtekrar test güvenilirliğinin çok yüksek ve Kısa Form-36 (fiziksel komponent) ve Hoehn-Yahr Evresi ile anlamlı ilişkisinin olduğu gösterilmiştir (71). Ankette her madde 0-4 arasında puanlanmakta ve yüksek puan yaşam kalitesinin iyi olduğunu göstermektedir.…”
Section: Parkinson Hastalığı Anketi-39 Ve Parkinsonunclassified